Personagem e voz na figura feminina dos romances de Ana Miranda e José Saramago - Abreu, Marizéte Borges de (2007)
In this work, we made a study of novels Desmundo of Ana Miranda and Memorial do Convento of José Saramago, specifically the narrative structure and feminine characters Oribela and Blimunda. The comparative method was used to promoving a dialogue between brazilian and portuguese literature. The authors made a History s critical revision, when through fiction, anonymous and stranger people had opportunity to show a new version of facts. In this way, the forgetful people and everyone who were quiet or had kept in silence by oficial history for years earned voice. The fictional procedures and organization of narratives reveal ideological marks of past that contrast with present, we have the time of history in direct confront with time of writing. Feminine characters are agents of social transformation, too. They keep themselves an ideological speech which approach them to the present. They look into their reality, and thought acute sense show us aspects of nature and human relationship had never seen before. The sensibility, capacity to appreciate the world and years of repression make the feminine characters a spokeswomen of excluded people such as poors, women and jewish beyond all persons who had an inadequate behaviour to pattern of period. Therefore, our purpose was reveal the manner as writters articulated literature elements mixing ideological aspects of present and past, history and fiction to build a ficcional universe which destroy the dominant ideology